2021
DOI: 10.1371/journal.pone.0253654
|View full text |Cite
|
Sign up to set email alerts
|

Black Americans demonstrate comparatively low levels of depression and anxiety during the COVID-19 pandemic

Abstract: Introduction During public health crises like the COVID-19 pandemic, populations can experience worsening mental health. Prior reports have suggested that Black Americans experienced lower rates of anxiety and depression than White Americans before the pandemic; however, during the pandemic, outcomes may be different as Black Americans have been disproportionately affected in terms of mortality, hospitalization, COVID-19 infection, and job loss. We documented the differential mental health impact of COVID-19 o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 24 publications
(19 citation statements)
references
References 38 publications
4
15
0
Order By: Relevance
“…( Goldmann et al , 2021 ) Another US study conducted during the COVID-19 pandemic using data from Understanding American Study also reached similar findings. ( Owens and Saw, 2021 ) A similar pattern has been reported that after 9/11, African American persons living in New York City during the disaster were less likely than NHW to suffer from depressions. ( Adams et al, 2006 )…”
Section: Discussionsupporting
confidence: 71%
See 4 more Smart Citations
“…( Goldmann et al , 2021 ) Another US study conducted during the COVID-19 pandemic using data from Understanding American Study also reached similar findings. ( Owens and Saw, 2021 ) A similar pattern has been reported that after 9/11, African American persons living in New York City during the disaster were less likely than NHW to suffer from depressions. ( Adams et al, 2006 )…”
Section: Discussionsupporting
confidence: 71%
“…Studies conducted during the pandemic period also support such findings. ( Goldmann et al , 2021 ; Owens and Saw, 2021 ) A US study using the same tool used in our study to measure anxiety and depression reported that during the COVID-19 pandemic, anxiety/depression was lower among NHB compared to NHW individuals. ( Goldmann et al , 2021 ) Another US study conducted during the COVID-19 pandemic using data from Understanding American Study also reached similar findings.…”
Section: Discussionmentioning
confidence: 88%
See 3 more Smart Citations